Сryoresistance of Autotrophic Organisms From Polar Regions Sensed by Chlorophyll Fluorescence Method - Giordano, Davide; Puhovkin, Anton; Hájek, Josef; Sekerák, Jiří; Bartak, Miloš (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):285